A tanyai lakosság szerepe és helye a vidéki élet vérkeringésében - Gálné Horváth, Ildikó (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The Great Hungarian Plain one of the - nowadays mentioned as a 'Hungaricum' in the literature - form of settlement; the population living on the farms occupies specific place in the Hungarian society. Before years - centuries - of collectivization of the agriculture inhabitants working in agriculture, earning money from it was understand in the literature. Nowadays all this an occupational construction, all of them all changed a lot in the look of commerce. The peasantry had its share of a determining role in the Hungarian society's establishment in the course of the centuries; let it be an economy, sociology, a tradition, etc. In the past twenty years did not let the farms untouched. New inhabitants, who reveal a quite heterogeneous picture to us considering their occupation, their conduct, their social role, appeared on the farms.